KONTROVERSI SEPUTAR PEMBAHARUAN HUKUM KELUARGA ISLAM DI INDONESIA - Yushadeni, Yushadeni (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2015)
Social movement from classic to modern demands changes included in the law. The law will not be progress if it was not changed and modernized. One law that is expected to contribute greatly to the reform laws in Indonesia is Islamic law. Islamic law is expected to give contribution in the reform of the current law, included in the family law of Islam. Actually , Islam gave a valuable contribution to reform of Islamic law in Indonesia with changing provisions of irrelevant islamic law. Nevertheless, the reforms caused controversy among Indonesia's Muslim community. The controversy about marriage ACT has happened since the time of colonization until this time and has resulted two groups, namely (1) female/feminist activist stronghold; and (2) the priest. During the new order period, negative feedback from the community of Muslims against the proposed legislation had to do with the Netherlands East Indies Government discretion castrate Islamic law. Although the Netherlands Indies Invaders have been expelled from Indonesia physically, but its concepts still entrenched in Indonesia. Meanwhile, in the reform era, is a symptom of religious fundamentalism is getting stronger. [Perkembangan sosial dari klasik hingga modern menuntut adanya perubahan termasuk dalam bidang hukum. Hukum tidak akan berkembang apabila hukum itu tidak diubah dan dimodernisasi. Salah satu hukum yang diharapkan memberikan kontribusi besar terhadap pembaruan hukum di Indonesia adalah hukum Islam. Hukum Islam diharapkan memberikan kontribusi dalam reformasi hukum saat ini, termasuk hukum keluarga Islam. Sebenarnya, Islam telah memberikan sumbangan berharga bagi perkembangan hukum Islam di Indonesia dengan mengubah ketentuan-ketentuan hukum yang tidak relevan. Meskipun demikian, pembaruan tersebut menimbulkan kontroversi di kalangan masyarakat Muslim Indonesia. Kontroversi UU perkawinan terjadi sejak masa penjajahan sampai saat ini dan menghasilkan dua kubu, yaitu (1) kubu aktivis perempuan/ feminis; dan (2) kubu agamawan. Pada masa orde baru, tanggapan negatif dari masyarakat muslim terhadap RUU ada kaitanya dengan kebijaksanaan Pemerintah Hindia Belanda yang mengebiri hukum Islam. Meskipun Penjajah Hindia Belanda telah diusir dari Indonesia secara fisik, tetapi konsep-konsepnya masih mengakar di Indonesia. Sementara itu, di era reformasi, gejala fundamentalisme agama semakin kuat.]